Chromium-Aluminide Coatings via Pack Cementation Method on Inconel 718 Alloy and Fe-Cr-Ni SuperAlloy - Tuba Yener (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
Inthis study, it is invastigated the low-temperature formation of chromiumaluminide coatings on a CrNiFe-base superalloy and Inconel 718 by packcementation process. A novel pack-aluminizing diffusion coating was applied at800°C during 4 and 6 hours.The chrom-aluminising powder packs were preparedusing aluminium and chromium powders as a source for depositing aluminium andchrominium, Al2O3 powder as an inert filler and ammoniumchloride NH4Cl as an activator. A scanning electron microscope (SEM)with energy dispersive X-ray spectrometer (EDS) and XRD were used tocharacterize the surface layers. SEM analysis revealed that coating layers werehomogenous, compact and nonporous and there was a good bonding at the interfaceof the coating and matrix. Layer thickness variation was changed from 11,17 to18,2 µm measured from the surface to the matrix. The hardness of the coatinglayer increased to 1000 HVN while the hardness of the matrix was 350 HVN withthe increasing process time.